Respuesta :
Answer:
The answer is : a. I and III
Step-by-step explanation:
- The effective rate of a loan (let's call it "e") can be calculated as: [tex]e=(1+\frac{i}{n})^n-1[/tex], where "i" is the nominal interest rate, and "n" is the number of compounding periods per year.
- When n equals one (n=1), which means that the number of compunding periods per year equals one (it compounds anually), then [tex]e=(1+\frac{i}{1})^1-1=i[/tex].
- Therefore , the anual nominal rate equals the effective rate ([tex]e=i[/tex]) when the interests compund anually.